Förskoleklasselever utforskar kombinatorik genom digitala animeringar - Andreas Ebbelind; Hanna Palmér; Kristina Danielsson; Emelie Patron; Marina Wernholm (Dalarna university, 2023)
The focus of this article is on digital tools as part of mathematics education with six-year-olds. More explicitly, we study how the creation of digital animations, as a part of working on a problem-solving task, enables young students' learning of combinatorics. In the article, the creation of digital animations implies that the students re-design, that is, recreate their solution procedure with a digital application. The aim with letting the young students create digital animations is diverse. We presume that such work enables problem solving as well as the learning of combinatorics, but also that it has potential to enable creativity and agency in learning. Video-documentations from three classrooms where students work on the problem-solving task were analysed from a multimodal perspective where teaching is seen as a design process. In that process, the teacher designs learning activities that give students access to different resources for their meaning making process. The results show that working with digital animations, when integrated in a learning design sequence, amplify students' learning of combinatorics.